Prophetic politics : Christian social movements and American democracy - Gutterman, David S. (Cornell University Press, 2005)
"What are the relationships among religion, politics, and narratives? What makes prophetic political narratives congenial or hostile to democratic political life? David S. Gutterman explores the prophetic politics of four twentieth- and twenty-first-century American Christian social movements: the Reverend Billy Sunday and his vision of "muscular Christianity"; Dr. Martin Luther King Jr. and the Civil Rights movement; the conservative Christian male organization Promise Keepers; and the progressive antipoverty organization Call to Renewal." "Gutterman develops a theory based on the work of Hannah Arendt and others and employs this framework to analyze expressions of the prophetic impulse in the political narrative of the United States. In the process, he examines issues about the tense and intricate relationship between religion and politics."--Jacket